Engineering Mathematics volume- IIA : for 2nd semester(CSE & IT) 3rd semester (ECE) - Pal, B.K (U.N. Dhur & Sons, 2021)
Engineering Mathematics volume- IIA : for 2nd semester(CSE & IT) 3rd semester (ECE) / Pal, B.K.. -- Kolkata: U.N. Dhur & Sons, 2021 510 P153e14v2A 14th ed No. of Copies : 1